The doctor will not see you now: investigating the social determinants of specialist care using the Canadian Longitudinal Study on Aging (CLSA) - Lan, Marie; Alemu, Feben W.; Ali, Shehzad (Frontiers in Public Health, 2024)
Background The Canada Health Act mandates universal access to medical services for all Canadians. Despite this, there are significant disparities in access based on socioeconomic status, race and ethnicity, immigrant status, and indigeneity. However, there is limited evidence on the use of specialist services among older adults in Canada. The primary objective of this study is to identify the associations of social determinants of health with access to medical specialist services for Canadians aged 45 years and older. The second objective is to identify the reasons for not being able to access the needed specialist care. Methods A cross-sectional analysis of the Canadian Longitudinal Study on Aging survey was conducted. Based on the Andersen’s model of health services use, a multivariable logistic regression model was used to evaluate the associations between ‘not being able to access the needed specialist service(s) in the last 12 months’ and individual-level sociodemographic determinants. Results Approximately 97% of those who required specialist care in the last year were able to visit a specialist. Of the participants who were not able to access the needed specialist services, about half (50.90%) were still waiting for a visit. The following factors were associated with greater difficulty in accessing specialist care: being younger (45-54 years), living in a rural area, having some post-secondary education, having a household income below $50,000 a year, not having a family physician, and having fair or poor perceived general health. Residents of British Columbia and Nova Scotia had a higher likelihood of reporting difficulty compared to those residing in Ontario. Conclusion While a majority of respondents were able to access specialist services when needed, those who had difficulty in accessing care were more likely to come from socially marginalized groups. Targeted policy interventions and improved health system coordination can reduce these barriers to care.